Determinants of fiscal multipliers revisited - Roman Horváth; Lóránt Kaszab; Ales Marsal; Katrin Rabitsch (Magyar Nemzeti Bank, 2019)
We generalize a simple New Keynesian model and show that a flattening of the Phillips curve reduces the size of fiscal multipliers at the zero lower bound (ZLB) on the nominal interest rate. The factors behind the flatting are consistent with micro- and macroeconomic empirical evidence: it is a result of, not a higher level of price rigidity, but an increase in the degree of strategic complementarity in price-setting - invoked by the assumption of a specific instead of an economy-wide labour market, and decreasing instead of constant-returns-to-scale. In normal times, the efficacy of fiscal policy and resulting multipliers tends to be small because negative wealth effects crowd out consumption, and because monetary policy endogenously reacts to fiscallydriven increases in inflation and output by raising rates, offsetting part of the stimulus. In times of a binding ZLB and a fixed nominal rate, an increase in (expected) inflation instead lowers the real rate, leading to larger fiscal multipliers. Conditional on being in a ZLB-environment, under a flatter Phillips curve, increases in expected inflation are lower, so that fiscal multipliers at the ZLB tend to be lower. Finally, we also discuss the role of solution methods in determining the size of fiscal multipliers.
Keywords: E52; E62; 330; fiscal multipliers; strategic complementarity; Phillips curve; zero lower bound; New Keynesian model